Placental haemodynamics: a computational study of maternal blood flow and oxygen transport in the human placenta - Blakey, Adam Matthew (2024)
In this thesis, we present mathematical models used to describe maternal blood flow and oxygen transport in the at-term human placenta. We take a computational approach using discontinuous Galerkin finite element methods, which allows us to expand upon previous work by considering a complex 2D placental geometry that respects the main structural features of the placenta.